2015
DOI: 10.1002/adem.201400426
|View full text |Cite
|
Sign up to set email alerts
|

Process‐ and Material‐Induced Surface Structures During Laser Polishing

Abstract: Laser polishing is a technique for smoothing the surface of metallic substrates. The roughness after polishing does not only contain remains of the initial surface roughness, it also contains new roughness due to surface structures, which are introduced by the polishing process. Since these structures greatly contribute to the roughness, it is necessary to understand the mechanisms that lead to their formation so as to prevent the structures from forming and allow higher smoothing of the surface. Hence, in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 4 publications
(4 reference statements)
2
34
0
Order By: Relevance
“…This causes the formation of bulges, which, in combination with the zigzag strategy, results in the shaping of the periodic structure perpendicular to the scanning direction. However, when overlap is high enough, this effect is no longer dominant, which proves the findings presented by Nüsser et al, as shown in Figure 8 b and Figure 9 b [ 14 ]. When higher overlaps are applied, energy density is increased exponentially, which results in higher local heat accumulation on the surface.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This causes the formation of bulges, which, in combination with the zigzag strategy, results in the shaping of the periodic structure perpendicular to the scanning direction. However, when overlap is high enough, this effect is no longer dominant, which proves the findings presented by Nüsser et al, as shown in Figure 8 b and Figure 9 b [ 14 ]. When higher overlaps are applied, energy density is increased exponentially, which results in higher local heat accumulation on the surface.…”
Section: Resultssupporting
confidence: 87%
“…The material’s relocation mechanism is linked with the laser thermal energy process (LP) and it might lead to the non-uniformity of the distribution of amplitudes (peaks and valleys). This is the result of the forming of material- and process-induced surface structures during melt-pool re-solidification [ 14 , 23 ]. Therefore, the Abbott–Firestone curve can be used to obtain information regarding the percentage distribution of the asperities over the analyzed surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mainly, continuous wave operating laser sources (cw) are used for macro-applications with remelting depths up to 200 µm. In contrast, pulsed laser sources (pw) are generally used for micro polishing with remelting depths of several micrometers [21]. Lambarri et al investigated the laser surface smoothing process of nickelbased alloys and were able to show a reduction in roughness as a function of the scanning speed and laser power using cw laser radiation [22].…”
Section: Introductionmentioning
confidence: 99%